Open Education : International Perspectives in Higher Education - Patrick Blessinger
Open Education provides a great mix of research and authentic application of "open" in éducation which is global in perspective. The contributions provide insightful evidence that open education as an ecosystem is on the tipping point of crossing the chasm from sharing to learn to learning to share. This book is a must-read for those who care about more sustainable education futures showing that open is a viable pathway to realising education as a fundamental human right. - Wayne Mackintosh, Founding Director of the OER Foundation and the OER Universitas In a time of openness vs closure, collaboration vs competition, elitism vs democratisation, this volume presents a range of perspectives that make a strong case for open education in both the developed and developing worlds. A recommended read for all those interested in transforming higher education. This book is a rich resource that illuminates the different dimensions of open education and its critical link to human rights. This delivers a very important message: that open education is a powerful tool to throw open the ivory towers and transform higher education in the 21st century. - Asha Kanwar, President & CEO, Commonwealth of Learning Sustainable Development Goal 4 (United Nations) enjoins us to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. While we cannot rely on our current rigid and closed educational traditions to meet this goal, the concepts of the open education movement provide some promise. The importance of this book lies in its analysis of these concepts through the lens of the democratisation of education. Open is taken to enable far more than access - rather it focuses in on ideals of diversity, inclusion, agency, equity and social justice, towards the final goal of improving learning for all. - Jenny Glennie, Head of Saide